Ambiguity values of the Philippine Thematic Apperception Test (PTAT) - Ventura, Elizabeth (Resurreccion) 1944- (Philippine Journal of Psychology, 1976)
The Philippine Thematic Apperception Test (PTAT) was randomly divided into three sections of eight cards each and administered via slide projection to 325 introductory psychology students (166 males and 159 females) at the University of the Philippines. Each subject told stories to four of the cards in English and the other four in Filipino with the language sequence reversed for succeeding groups so that, in effect, equal numbers of students told stories in the English Filipino and Filipino-English sequences. An average of fifty students told stories either in English or in Filipino to the same card. The stories were scored for the sex of the characters, their age, relationship (if any), what was happening, why this was happening and how the story ended. The relative measure of uncertainty (H) was obtained for each aspect of the PTAT story for each card. Analysis of the results reveal that (1) Ends are significantly more 'ambiguous in Filipino that in English; (2) Male subjects in the study have significantly more ambiguous story endings in English than in Filipino; (3) the foregoing findings are further supported by Spearman's rank correlation coefficients demonstrating that male and female responses are essentially associated except for the End and Alii variables: (4) Cards depicting Male. Only yield higher ambiguity scores for the Why variable compared to cards with No Person. in Filipino and cards with Both sexes. in English; (5) the degree to which certain variables are emphasized in the stories appear to be the same under both language conditions. Although various explanations have been advanced for these findings, level of explicitness may be a confounding factor in this study.